The Multiple Mechanisms by Which Watching Dramas Can Repair or Enhance Moods. Issue 1 (1st January 2023) - Chang, Chingching
ABSTRACT: This article seeks to explain the mood repair process that sad viewers undergo and the mood enhancement process that happy viewers adopt when they watch drama series with varying levels of likability and familiarity. Building on the idea that drama enjoyment can regulate moods, the authors test three possible processes: transportation path (involving transportation and enjoyment), meaning path (involving transportation, moved feelings, thought reflections, and enjoyment), and parasocial support path (involving transportation, parasocial interactions, identification with drama characters, and enjoyment). The findings identify likability as crucial and also show that the processes vary for happy versus sad viewers.